COMPARATIVE ANALYSIS OF POWER SPECTRAL DENSITY ON EEG SIGNALS OF WET AND DRY ELECTRODES USING AUDIO STIMULUS - Faadhilah Afif, Nur
Electroencephalography (EEG) electrodes are divided into two types: dry and wet. The wet electrode has an impedance value of 5-20 kW, while the dry electrode has an impedance value of 16 kW. Impedance value of Scalp surface is 200kW. The large impedance difference between the electrode and the surface of the scalp can cause a loss signal. A loss signal can affect the characteristics of Power Spectral Density (PSD). This study is aimed to analysis PSD from wet and dry electrodes in Alpha and Beta frequency. This study was conducted using Emotiv EPOC (wet) and Insight (dry). The temporal (T7 and T8) and anterior frontal (AF3 and AF4) electrodes from both devices were used to be compared. An audio stimulus that contains a story was chosen followed by a small task related to the story. The data acquisition was performed on 8 subjects for 36 minutes: 3 minutes before, 30 minutes during, and 3 minutes after giving an audio stimulus. The data analysis methods include pre-processing the signal using the centering and bandpass filter process and PSD calculations using the Welch periodogram with the Hanning window. PSD calculation results show that the percentage difference in the average value of the highest and lowest PSD changes on the wet electrode is greater than the dry electrode.